SIMILARITIES AND DIFFERENCES BETWEEN UZBEK AND ENGLISH PLURAL SUFFIXES - Razzoqova Shahlo Baxtiyor qizi; Murodova Muxlisa Tursunboyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article examines the similarities and differences between Uzbek and English plural suffixes. Plural formation is a fundamental aspect of grammar, and understanding its mechanisms in different languages highlights both linguistic universals and language-specific features. Uzbek, a member of the Turkic language family, and English, a Germanic language, utilize distinct morphological processes to express plurality. While English predominantly employs the suffixes "-s" and "-es," Uzbek relies on vowel harmony in suffixes like "-lar" and "-ler." This study compares their phonological, morphological, and syntactic properties, exploring their respective rules, exceptions, and usage in linguistic contexts. The findings shed light on how these languages handle plurality, contributing to comparative linguistic studies and aiding language learners in mastering pluralization rules.